Craniovertebral Angel Changes as a Consequence of Scapular Strengthening Exercise: A Randomized Control Trial - Ibrahim, Dalia M.; Gomaa, Ebtessam F.; Azzam, Ahmad H.; Fayaz, Nadia A. (International Journal of Psychosocial Rehabilitation, 2020)
Scapular postural correction strategies have been advocated as part of the intervention for patients with neck pain who display an alteration in scapular orientation affecting the head posture. The purpose of this study is to examine the effect of scapular retractors strengthening exercise on craniovertebral angle (CVA) in patients with chronic mechanical neck pain. Thirty patients participated in this study and they were randomly assigned into 2 groups: Group (A) (experimental group): consisted of 15 patients who received scapular retractors strengthening program with traditional physical therapy treatment. Group (B) (control group): consisted of 15 patients who received only the traditional physical therapy treatment in the form of (infrared, activation of deep neck flexors, isometric exercises, and stretching exercises) both groups received treatment for 18 sessions over 6 weeks’ period. The CVA was measured before and after intervention. Statistical analysis showed that there was no significant difference in the CVA post treatment between the study and control groups (p>005). Conclusions: The combined effect of scapular retractors strengthening program with traditional physical therapy treatment had no significant improvement on forward head posture (CVA) than the traditional therapy treatment alone.